Effect of age of seedlings at staggered transplanting and nutrient management on yield performance of aromatic fine rice (cv. BRRI dhan38) (SAARC Journal of Agriculture, 2018)
An experiment was conducted at the Agronomy Field Laboratory, Bangladesh Agricultural University, Mymensingh during July to December 2014 with a view to finding out the effect of age of seedlings at staggered transplanting and nutrient management on growth and yield of aromatic fine grained rice (cv. BRRI dhan38). The experiment consisted of three ages of seedlings (30, 45 and 60 day-old) at staggered transplanting and six nutrient managements viz. control (no nutrients), recommended dose of inorganic fertilizers, 50% of recommended dose of inorganic fertilizers + cowdung @ 5 t ha-1, 75% of recommended dose of inorganic fertilizers + cowdung @ 5 t ha-1, 50% of recommended dose of inorganic fertilizers + poultry manure @ 2.5 t ha-1 and 75% of recommended dose of inorganic fertilizers + poultry manure @ 2.5 t ha-1. The experiment was laid out in a randomized complete block design with three replications. The effect of age of seedlings at staggered transplanting, nutrient management and their interactions were significant on crop characters, yield components and yield of aromatic fine rice. The tallest plant was recorded due to transplanting 30- day old seedlings fertilized with 75% of recommended dose of inorganic fertilizers + poultry manure @ 2.5 t ha-1. The highest leaf area index (6.55), number of total tillers hill-1 (12.56), number of effective tillers hill-1 (8.54), panicle length (24.07cm) and number of grains panicle-1 (141.3) were recorded in 30-day old seedlings fertilized with 75% of recommended dose of inorganic fertilizers + poultry manure @ 2.5 t ha-1 while the lowest values were recorded in 60-day old seedling with control. In case of sterile spikelets panicle-1, 60-day old seedlings with control treatment showed the highest value (30.94). The highest grain (3.85 t ha-1) and straw (5.29 t ha-1) yields were obtained in 30-day old seedlings fertilized with 75% of recommended dose of inorganic fertilizers + poultry manure @ 2.5 t ha-1. Therefore, 30-day old seedlings fertilized with 75% of recommended dose of inorganic fertilizers + poultry manure @ 2.5 t ha-1 appeared as the promising technique for appreciable growth and grain yield of aromatic fine grained rice (cv. BRRI dhan38).SAARC J. Agri., 16(1): 49-59 (2018)